2021
DOI: 10.3390/ijms22168694
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Signaling Promotes the Secondary Growth of Storage Roots in Panax ginseng

Abstract: Gibberellins (GAs) are an important group of phytohormones associated with diverse growth and developmental processes, including cell elongation, seed germination, and secondary growth. Recent genomic and genetic analyses have advanced our knowledge of GA signaling pathways and related genes in model plant species. However, functional genomics analyses of GA signaling pathways in Panax ginseng, a perennial herb, have rarely been carried out, despite its well-known economical and medicinal importance. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…One of the key elements that influences the yield and quality of P. ginseng is the promotion of secondary growth of the storage roots. Recent research has demonstrated that treatments with exogenous nitrate or gibberellins (GAs) significantly accelerated the storage root secondary growth of P. ginseng (Geem et al 2022;Hong et al 2021b). In these studies, the protein-protein interaction network analysis of two secondary growth promoting factors revealed that the auxin activated signaling pathway would be fundamentally integrated into the hormonal regulation networks for storage root formation (Geem et al 2022;Hong et al 2021b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key elements that influences the yield and quality of P. ginseng is the promotion of secondary growth of the storage roots. Recent research has demonstrated that treatments with exogenous nitrate or gibberellins (GAs) significantly accelerated the storage root secondary growth of P. ginseng (Geem et al 2022;Hong et al 2021b). In these studies, the protein-protein interaction network analysis of two secondary growth promoting factors revealed that the auxin activated signaling pathway would be fundamentally integrated into the hormonal regulation networks for storage root formation (Geem et al 2022;Hong et al 2021b).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has demonstrated that treatments with exogenous nitrate or gibberellins (GAs) significantly accelerated the storage root secondary growth of P. ginseng (Geem et al 2022;Hong et al 2021b). In these studies, the protein-protein interaction network analysis of two secondary growth promoting factors revealed that the auxin activated signaling pathway would be fundamentally integrated into the hormonal regulation networks for storage root formation (Geem et al 2022;Hong et al 2021b). To further investigate the core genetic networks affecting the auxin-connected storage root thickening process in P. ginseng, we reanalyzed the RNA-seq data of nitrate-treated roots of 1-year-old P.ginseng (Geem et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, chorismate mutase and 4-aminobenzoate synthase were somewhat up-regulated throughout the observed time course, whereas 4-coumarate CoA ligase was up-regulated at later time points. In studies aiming to identify browning phenotype-correlated genes through combining genetic analysis and QTL, many QTLs included melanin biosynthesis pathway genes such as CM, PALs, and PPOs [ 46 , 47 ]. These findings confirm our explanation of how browning is regulated and further indicate that targeting these genes in molecular breeding methods such as CRISPR-Cas9 might lead to browning-insensitive types.…”
Section: Discussionmentioning
confidence: 99%
“…Gene Ontology (GO) term was inferred from manually annotated data from the A. bisporus JB137 database, and enriched GO terms were determined based on EASE score from a modified Fisher’s exact test, p < 0.05 [ 40 , 41 , 42 ]. Enriched GO genes were further analyzed with Gene Set Enrichment Analysis (GSEA), as described in Hong et al [ 43 , 44 , 45 , 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Gene ontology (GO) term enrichment analysis was performed using DAVID [ 67 ], and enriched GO terms were determined by Fisher’s exact test ( p < 0.05). Enriched GO genes were further analyzed with gene set enrichment analysis (GSEA, v4.1.0, US), as in [ 68 , 69 ]. Network analysis was performed with GeneMANIA app (v3.5.2, US) in Cytoscape (v3.9.0, US) [ 70 , 71 ] with WRKY44 as query gene.…”
Section: Methodsmentioning
confidence: 99%